2021
DOI: 10.3390/app12010407
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Truss Topology and Sizing Optimization by an Improved Genetic Algorithm with Multipoint Approximation

Abstract: Truss size and topology optimization problems have recently been solved mainly by many different metaheuristic methods, and these methods usually require a large number of structural analyses due to their mechanism of population evolution. A branched multipoint approximation technique has been introduced to decrease the number of structural analyses by establishing approximate functions instead of the structural analyses in Genetic Algorithm (GA) when GA addresses continuous size variables and discrete topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…U ′ e is the electric potential applied to a piezoelectric beam element. Using Equations ( 15), ( 19) and (20), the potential energy in a piezoelectric beam element can be further expressed as…”
Section: Variation Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…U ′ e is the electric potential applied to a piezoelectric beam element. Using Equations ( 15), ( 19) and (20), the potential energy in a piezoelectric beam element can be further expressed as…”
Section: Variation Formulationmentioning
confidence: 99%
“…The random search algorithm is another type of optimization method for shape control problems. Dong and Huang [20] optimized a truss topology based on a multipoint approximate function and a Genetic Algorithm (GA). An optimized actuator was positioned for an adaptive truss using a two-level multipoint approximation method [21].…”
Section: Introductionmentioning
confidence: 99%
“…From the moment it was introduced to the literature, the genetic algorithm (GA) has been used for all kinds of optimization problems. In this section, a GA focused on truss optimization in recent years is presented [39][40][41][42][43][44][45][46]. Assimi et al [39] used the GA to minimize the cross-section area of truss systems; Liu and Xia [40] proposed a hybrid intelligent genetic algorithm (HIGA) and reported that the new method is a convenient tool for truss optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Assimi et al [39] used the GA to minimize the cross-section area of truss systems; Liu and Xia [40] proposed a hybrid intelligent genetic algorithm (HIGA) and reported that the new method is a convenient tool for truss optimization. Noii et al [41] and Dong et al [42] proposed a new approach to improve the GA, while Delyová et al [43] used the GA for size and topology optimization, and Assimi et al [46] introduced a new mutant operator for the GA.…”
Section: Introductionmentioning
confidence: 99%